2016
DOI: 10.1159/000450626
|View full text |Cite
|
Sign up to set email alerts
|

Local Recurrence after Breast-Conserving Surgery and Mastectomy Following Neoadjuvant Chemotherapy for Locally Advanced Breast Cancer - a Meta-Analysis

Abstract: Background: Breast-conserving surgery (BCS) in patients with large tumors shrunk by neoadjuvant chemotherapy (NCT) remains controversial. We conducted a meta-analysis to evaluate the local recurrence rates in locally advanced breast cancer (LABC) patients receiving NCT comparing BCS with mastectomy. Methods: Pubmed, Web of Knowledge, and Ovid's database were searched for studies concerning treatment for LABC from January 2000 to June 2015. A meta-analysis was performed to compare the recurrence rates of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 31 publications
1
25
1
1
Order By: Relevance
“…LRFS and DRFS were not significantly different between the BCS and MT groups [ 34 , 35 ] as well as like some studies said, following neoadjuvant chemotherapy [ 36 , 37 ]. However, some researchers found that BCS patients had higher LR after NAC, perhaps because the surgical margins became difficult to accurately assess [ 38 ], some studies reported contrary results that MT group had higher LR rate compared with BCS group [ 18 , 39 ].…”
Section: Discussionmentioning
confidence: 79%
“…LRFS and DRFS were not significantly different between the BCS and MT groups [ 34 , 35 ] as well as like some studies said, following neoadjuvant chemotherapy [ 36 , 37 ]. However, some researchers found that BCS patients had higher LR after NAC, perhaps because the surgical margins became difficult to accurately assess [ 38 ], some studies reported contrary results that MT group had higher LR rate compared with BCS group [ 18 , 39 ].…”
Section: Discussionmentioning
confidence: 79%
“…The long-term survival rate among early breast cancer women without NAC who undergo BCS was the same as that among women who undergo radical mastectomy [6][7]. However, several studies have demonstrated no signi cant difference in long-term survival or local recurrence rates between women who underwent BCS and those who underwent radical mastectomy after NAC [8][9]. Although predictive factors for local recurrence in these NAC-treated patient groups have not yet been clari ed yet, the higher local recurrence risk of NAC than of adjuvant chemotherapy is controversial.…”
Section: Introductionmentioning
confidence: 93%
“…Recent evidences seem to refute initial data. In their 2017 metanalysis, Zhou and colleagues reviewed 2000-2015 literature selecting eight trials, with a total of 3,215 patients analyzed: 1,361 receiving BCS and 1,854 who underwent mastectomy (68). At 5 years follow-up, the prevalence of local recurrence was 9.2% in the BCS group, versus 8.3% in the mastectomy group and overall survival was significantly higher in the BCS group, confirming response to NACT a major prognostic factor.…”
Section: Factors Related To Lacking Evidences In Surgical Breast Consmentioning
confidence: 99%